Sintesis, Karakterisasi Nanopartikel Magnetit, Mg/Al NO3 –Hidrotalsit dan Komposit Magnetit-Hidrotalsit - Fajar Indah Puspita Sari (Syarif Hidayatullah State Islamic University, 2017)
Synthesis and characterization magnetite, Mg/Al NO3- hydrotalcite and magnetite-hydrotalcite have been done. The XRD and FTIR characterization result from third compound is used to assess the conformation of magnetite in the structure of hydrotalcite by comparison of spectra. Obtained that magnetite nanoparticles (10-20 nm) dispersed on octahedral lattice of hydrotalcite. The position investigation of magnetite particles in the hydrotalcite structure is very useful to determining applications of this composite in various fields, especially that involve ion exchange feature from hydrotalcite.DOI: http://dx.doi.org/10.15408/jkv.v0i0.4526